The Girls Set the Tone: Gendered Classroom Norms and the Development of Aggression in Adolescence. (May 2015) - Busching, Robert; Krahé, Barbara
In a four-wave longitudinal study with N = 1, 321 adolescents in Germany, we examined the impact of class-level normative beliefs about aggression on aggressive norms and behavior at the individual level over the course of 3 years. At each data wave, participants indicated their normative acceptance of aggressive behavior and provided self-reports of physical and relational aggression. Multilevel analyses revealed significant cross-level interactions between class-level and individual-level normative beliefs at T1 on individual differences in physical aggression at T2, and the indirect interactive effects were significant up to T4. Normative approval of aggression at the class level, especially girls' normative beliefs, defined the boundary conditions for the expression of individual differences in aggressive norms and their impact on physically and relationally aggressive behavior for both girls and boys. The findings demonstrate the moderating effect of social norms on the pathways from individual normative beliefs to aggressive behavior in adolescence.